Genetic Variation Predicts Serum Lycopene Concentrations in a Multiethnic Population of Postmenopausal Women. Issue 2 (3rd December 2014) - Zubair, Niha; Kooperberg, Charles; Liu, Jingmin; Di, Chongzhi; Peters, Ulrike; Neuhouser, Marian L
Abstract: Background: The consumption and blood concentrations of lycopene are both positively and inversely associated with the risk of several chronic diseases. The inconsistences in lycopene disease association studies may stem from a lack of knowledge about the genetic variation in the synthesis, metabolism, and deposition of transport and binding proteins, which potentially influence serum lycopene concentrations. Objective: We examined the association between variation across the genome and serum concentrations of lycopene in a multiethnic population. Methods: Participants included African ( n = 914), Hispanic ( n = 464), and European ( n = 1203) American postmenopausal women from the Women's Health Initiative. We analyzed ∼7 million single nucleotide polymorphisms (SNPs). Linear regression models were used to assess associations between each SNP and serum concentrations (log transformed, continuous) of lycopene; we adjusted for age, body mass index, and population substructure. Models were run separately by ethnicity, and results were combined in a transethnic fixed-effects meta-analysis. Results: In the meta-analysis, the scavenger receptor class B, member 1 ( SCARB1 ) gene, which encodes for a cholesterol membrane transporter, was significantly associated with lycopene concentrations (rs1672879; P < 2.68 × 10 −9 ). Each additional G allele resulted in a 12% decrease in lycopene concentrations for African Americans, 20% decrease for Hispanic Americans, and 9% decrease for European Americans. In addition, 2 regions were significantly associated with serum lycopene concentrations in African Americans: the slit homolog 3 gene ( SLIT3 ), which serves as a molecular guidance cue in cellular migration, and the dehydrogenase/reductase (SDR family) member 2 ( DHRS2 ) gene, which codes for an oxidoreductase that mitigates the breakdown of steroids. Conclusions : We found 3 novel loci associated with serum lycopene concentrations, 2 of which were specific to African Americans. Future functional studies looking at these specific genes may provide insight into the metabolism and underlying function of lycopene in humans, which may further elucidate lycopene's influence on disease risk and health. This trial was registered at clinicaltrials.gov as NCT00000611.